Big impact on small children: child-care providers' perceptions of their role in early childhood healthy lifestyle behaviours. Issue 2 (3rd April 2017) - Sisson, Susan B.; Smith, Chelsea L.; Cheney, Marshall
ABSTRACT: The purpose of this study is to examine childcare providers' perceptions of their role in child health behaviors and attitudes pertaining to physical activity and nutrition. Part and full-time providers in a childcare center or family childcare home were interviewed ( n  = 30) in this cross-sectional, qualitative study. Transcripts were digitally recorded, transcribed, coded, and analyzed for general themes and sub-themes using a grounded theory by three investigators. All participants were women (100%), and most were employed full time (73%). Four general themes were identified with sub-themes: 1) teachers' perceptions of their role; 2) teachers' perceptions of lack of consistency between home and school; 3) teachers' attitudes and beliefs about movement and; 4) teachers' attitudes about food, feeding, and child nutrition. Providers emphasized their care-giving role and did not identify their role in shaping health behaviors. Engaging with parents is indispensable, but providers are often frustrated with parents' double standards. They felt that movement was important, but that children were sufficiently active. Teachers encouraged eating, but acknowledged personal struggles with good nutrition. Empowering childcare teachers to serve as role models for all healthy behaviors may benefit child and teacher wellness.